The high field side high density region in SOLPS-modeling of nitrogen-seeded H-modes in ASDEX Upgrade. (August 2017) - Reimold, F.; Wischmeier, M.; Potzel, S.; Guimarais, L.; Reiter, D.; Bernert, M.; Dunne, M.; Lunt, T.; ,; ,
Abstract: The understanding of divertor physics and the evolution of divertor detachment is crucial for developing the capability to model power exhaust in current experiments and reliably predict it for future fusion devices. In simulations of ASDEX Upgrade, an experimentally observed region of high density in the high field side scrape-off layer has been recovered. Validated modeling with SOLPS5.0 shows that a detailed match of the high field side scrape-off layer plasma is not only important for local plasma parameters, but can lead to strong changes in global parameters. Drifts play a crucial role in lower-single null discharges with forward toroidal field ( ∇ B → -drift pointing down). Their inclusion changes the spatial extent as well as the radial and poloidal gradients of the high field side high density. Adapted transport coefficients that take into account core fueling by plasma diffusion due to the presence of the high field side density and drift-driven radial fluxes now reconcile the modeled deuterium compression ratio, divertor neutral density, neutral radiation levels and deuterium fueling rates with experimental measurements. The onset of strong volume recombination in the simulations now allows to remove the previously necessary increase of perpendicular transport in the inner divertor from the simulations.